GDNF–Ret signaling in midbrain dopaminergic neurons and its implication for Parkinson disease. Issue 24 (7th November 2015) - Kramer, Edgar R.; Liss, Birgit
Abstract : Glial cell line‐derived neurotrophic factor (GDNF) and its canonical receptor Ret can signal together or independently to fulfill many important functions in the midbrain dopaminergic (DA) system. While Ret signaling clearly impacts on the development, maintenance and regeneration of the mesostriatal DA system, the physiological functions of GDNF for the DA system are still unclear. Nevertheless, GDNF is still considered to be an excellent candidate to protect and/or regenerate the mesostriatal DA system in Parkinson disease (PD). Clinical trials with GDNF on PD patients are, however, so far inconclusive. Here, we review the current knowledge of GDNF and Ret signaling and function in the midbrain DA system, and their crosstalk with proteins and signaling pathways associated with PD.